Melek Zaman Bergerak Mapan: Perubahan Sosial dan Ekonomi Masyarakat Kampung Adat Cirendeu dalam Proses Modernisasi - M. Raihan Ardiansyah; Mochamad Arif Rahman; Rahmayanti Nur Malika; Bella Carolina Hutasoit; Guntur Bayu Julianto; Aditya Firmansyah; Nenden Siti Khodijah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This article examines the socio-economic transformation of the Cirendeu Indigenous Community as it navigates the pressures and opportunities of modernization. Using a descriptive qualitative approach supported by literature studies and secondary data, the research explores how Cirendeu maintains cultural identity while adapting to evolving economic demands. The study finds that the community has successfully diversified its economic activities, shifting from subsistence practices toward broader engagement in food production, local trade, and cultural tourism. Cassava-based products, historically central to Cirendeu’s food system, have developed into valuable economic commodities that strengthen food resilience and generate new income sources. In parallel, carefully managed tourism activities contribute to the local economy without disrupting customary values. Socially, the community continues to uphold traditional norms that regulate collective life, ensuring that modernization does not erode cultural cohesion. Overall, this study highlights Cirendeu’s ability to integrate local economic potential within a modern framework while sustaining autonomy, cultural continuity, and community well-being.